E. A. Poe and A. A. Shkljarevskij: Foregrounding Deduction and/or Social Commentary – A Comparative Study of Early Detective Fiction - Maja Pandžić ([sic])
Three decades after American author Edgar Allan Poe laid down the foundations for the detective genre in the 1840s with his “tales of ratiocination,” native detective stories began to appear on Russian literary scene. Among them were those written by Aleksandr Andreevich Shkljarevskij today known as “the father of Russian detective fiction.” This article provides a short overview of Poe’s literary influence as well as of the conditions that brought about the onset of Russian detective fiction. It offers an extensive comparative analysis of short stories by the mentioned “fathers” and identifies many similarities in their poetics. Finally, by looking into the characteristics of American Romanticism and Russian Realism that constitute the sociocultural backgrounds of the authors, it proposes answers to questions stemming from the difference in the aspect of analysis they emphasize. Keywords: 19th century Russian detective fiction, Edgar Allan Poe, Aleksandr Andreevich Shkljarevskij, social criticism, ratiocination, crime fiction